2007
DOI: 10.1111/j.1399-5618.2007.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following a first manic episode: cross‐national US and Taiwan comparison

Abstract: The early course of BD varies between Chinese and American patients. Some of this variance results from demographic and clinical cross-national differences in premorbid variables. Other sources of variance remain to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…table 1). The representativeness of the overall sample was mirrored by the fact that several studies covered more than one geographical area; for example, Strakowski et al [26] reported on relapses and recurrences of 2 independent samples from Cincinnati and Taipei, and the so-called EMBLEM study [27] included 530 investigators across 14 European countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…table 1). The representativeness of the overall sample was mirrored by the fact that several studies covered more than one geographical area; for example, Strakowski et al [26] reported on relapses and recurrences of 2 independent samples from Cincinnati and Taipei, and the so-called EMBLEM study [27] included 530 investigators across 14 European countries.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some of the excluded studies had samples that overlapped with those of the included studies. Finally, 12 studies were eligible for inclusion in the meta-analysis [4,6,8,11,23,24,25,26,27,28,29,30](online suppl. table 1).…”
Section: Resultsmentioning
confidence: 99%
“…All the participants underwent direct interviews, which two of the experienced psychiatrists involved in this study conducted using the Chinese version of the Structured Clinical Interview (for the DSM-III-R Patient Edition) [18] to confirm the diagnosis of bipolar I disorder in addition to any prior history of psychiatric disorders. We simultaneously administered the WCST, measured hs-CRP and carried out brain MRI in the bipolar patients who had achieved DSM-IV-defined remission, that is, those who had Young Mania Rating Scale total scores <5 and Hamilton Depression Rating Scale total scores <7 continuously for 2 months [19]. …”
Section: Methodsmentioning
confidence: 99%
“…After an overnight fast beginning at 24:00 h, BD-A patients and control subjects provided blood samples between 08:30 h and 09:30 h in the following morning. Follow-up blood samples of the same manic patients in remission (BD-R) were collected, that is, when they had Young Mania Rating Scale scores of Ͻ5 and Hamilton Depression Rating Scale-21 scores of Ͻ7 (33). Heparinized blood was drawn by venous puncture.…”
Section: Plasmamentioning
confidence: 99%